Operations training wastewater treatment course - Water Environment Federation (U.S.) (Alexandria, Va. Water Environment Federation, 1996)
This course is designed to help you improve your skills as a wastewater treatment plant operator, and to increase your knowledge of the processes and procedures common to all treatment plants
The Operations Training course is divided into 9 units of which 8 deal with actual course content issues. The other unit serves as an online help system, introducing the program and demonstrating its use.
Text
System Requirements : Pentium @ 90 MHz or faster, 16 MB RAM or more, 30 MB free hard disk space, CD-ROM drive 4x or faster, sound card with speakers, SVGA (16 million colors) display with hardware video acceleration.
Keywords: Sewage -- Purification; Sewage disposal; Sewage disposal plants